2014
DOI: 10.1002/mc.22158
|View full text |Cite
|
Sign up to set email alerts
|

Reduced retinoids and retinoid receptors' expression in pancreatic cancer: A link to patient survival

Abstract: Pancreatic ductal adenocarcinoma (PDAC) represents one of the deadliest cancers in the world. All-trans retinoic acid (ATRA) is the major physiologically active form of vitamin A, regulating expression of many genes. Disturbances of vitamin A metabolism are prevalent in some cancer cells. The main aim of this work was to investigate deeply the components of retinoid signaling in PDAC compared to in the normal pancreas and to prove the clinical importance of retinoid receptor expression. For the study, human tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 51 publications
0
41
1
1
Order By: Relevance
“…Bleul et al [107] claim that endogenous retinoids inhibit carcinogenesis and the beneficial effect of retinoid treatment should depend on the expression level of retinoid receptors in tumour tissue. A reduction of retinoids and their receptors is an important feature of pancreatic cancer and is associated with worse patient survival outcomes [107].…”
Section: Retinoidsmentioning
confidence: 99%
“…Bleul et al [107] claim that endogenous retinoids inhibit carcinogenesis and the beneficial effect of retinoid treatment should depend on the expression level of retinoid receptors in tumour tissue. A reduction of retinoids and their receptors is an important feature of pancreatic cancer and is associated with worse patient survival outcomes [107].…”
Section: Retinoidsmentioning
confidence: 99%
“…We downloaded this set from the Lnc2Cancer database, and a total of nine pancreatic-cancer associated lncRNAs were identified in the CNC network (Supplementary Table S6). With FDR < 0.01, LncRNAs2Pathways obtained seven statistically significant pathways (Table 3), examples of which include the following: arachidonic acid metabolism, in which lipoxygenases, which are the key constituents, play a critical role in pancreatic cancer cell proliferation63; oxidative phosphorylation, whose KCa3.1 channel was identified as a regulator in a subset of pancreatic carcinoma cell lines64; the reduction of retinoids and their receptors, which is associated with pancreatic cancer patient survival65; and the overexpression of ribosomal proteins, which can promote tumorigenesis by interacting with the p53 tumor suppressor66. For the significant pathways, such as arachidonic acid metabolism, 14 core genes were identified (Supplementary Figure S4A).…”
Section: Resultsmentioning
confidence: 99%
“…Expression of the retinoid receptor was determined by QuantiFast SYBR Green PCR kit (Qiagen, Hilden, Germany) following the manufacturer's instruction and described elsewhere [24]. Briefly, 1 µl of cDNA synthesized before was added to reaction mix in 96-well plate.…”
Section: Sybr Green Quantitative Pcr For Retinoid Receptormentioning
confidence: 99%
“…In our previous study, we showed that the down-regulation of retinoid receptors in PDAC is negatively correlated with patient survival, which indicates that retinoid receptors could function as tumor suppressors [24]. To investigate whether retinoid receptor mRNAs are targeted by specific miRNAs, the first step is to predict the specific binding sites in the 3'UTRs.…”
Section: Prediction Of Retinoid Receptor Sequences Targeted By Mirnasmentioning
confidence: 99%